The Effect Of NPL, ROE, CAR On Price Earning Ratio On Commercial Banks In Indonesia - Yusuf Iskandar; Achmad Zaki; Sinollah Sinollah (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
Economic development in Indonesia can have an influence on companies, especially service companies such as banks. Seeing the development of service companies such as banks that continue to fluctuate, this can have an impact on the performance of banking companies on the price earning ratio, therefore a research can be carried out aimed at examining the effect of non-performing loans, return on equity, and capital adequacy ratios on price earnings. ratio in commercial banks in Indonesia. The analytical tool in this study using multiple regression analysis. Data analysis was carried out on banking companies listed on the Indonesian stock exchange in 2017 - 2019. A total of 15 banks that met the criteria as members of the study population, all members of the population were used as research samples. The results of this study indicate that non-performing loans have a significant effect on the price earning ratio, return on equity has a significant effect on the price earning ratio, and the capital adequacy ratio has a significant effect on the price earning ratio